If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7) = (x + 9) * 2 Multiply 2 * 7 14 = (x + 9) * 2 Reorder the terms: 14 = (9 + x) * 2 Reorder the terms for easier multiplication: 14 = 2(9 + x) 14 = (9 * 2 + x * 2) 14 = (18 + 2x) Solving 14 = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 14 + -2x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 14 + -2x = 18 + 0 14 + -2x = 18 Add '-14' to each side of the equation. 14 + -14 + -2x = 18 + -14 Combine like terms: 14 + -14 = 0 0 + -2x = 18 + -14 -2x = 18 + -14 Combine like terms: 18 + -14 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| 173-5x=40x+18 | | 7t-4*2t+3t*4/2 | | 10+p=3 | | 6-2(4x)+7=0 | | 5(-2)=y+6 | | 7a*3a= | | 5(0)=y+6 | | 4-9p=49 | | 3/4+5/3 | | 5(2)=y+6 | | 9*n=53 | | 2y-6.2+y=8.8 | | -4+8X=5+2X | | 2(m+5)=28 | | 12+(21-6)/3 | | (4y+3)-(-3y-6)=-2 | | -2(6)+9=-(9)-3 | | -2(-12)+9=-(0)-3 | | 4(x-6)+2=6x-6 | | 5x-1+-2x+7=9 | | 65-98+(85-6x)=9 | | (9x^3-4x^2+3x)-(7x^2+2x+4)= | | 3x/4-21x/32=9/8 | | 12.4=9+t | | -2(2)+9=-(-4)-3 | | 4(y-1/2)=y-6(5-Y) | | 3x/4-21x/32=-11/8 | | 4=-5/x-6 | | 10x+28=4x+178 | | (9b-5)-4(2b+2)=-3 | | 4x-8=-11 | | -5(3)+15=-10(3) |